2019
DOI: 10.1590/2177-6709.24.6.036-047.oar
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment with passive eruption and mesialization of semi-impacted mandibular third molar in an adult with multiple dental losses

Abstract: Objective: This article describes the orthodontic treatment performed on an adult patient with multiple dental losses. Case report: A female patient, 20 years and 4 months old, presented with the following conditions: absence of teeth #26, #35, #36 and #46; semi-impacted tooth #48; inclined molars adjacent to an edentulous space; canines and premolars in a Class II relationship; a convex profile; biprotrusion; and forced lip sealing. Results: Space in the region of tooth #26 was closed, as well the space of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…7-N° 2, 2023, pp. 1201-1214 Journal Scientific MQRInvestigar 1208 el estado periodontal puede agravarse, con signos de inflamación, pérdida ósea angular y una bolsa aparente en la superficie mesial de un molar mandibular inclinado (Lindskog-Stokland et al, 2013;Saga et al, 2019;Zoizner et al, 2018).…”
Section: Resultados áReas Diagnóstico En Mesialización Molarunclassified
“…7-N° 2, 2023, pp. 1201-1214 Journal Scientific MQRInvestigar 1208 el estado periodontal puede agravarse, con signos de inflamación, pérdida ósea angular y una bolsa aparente en la superficie mesial de un molar mandibular inclinado (Lindskog-Stokland et al, 2013;Saga et al, 2019;Zoizner et al, 2018).…”
Section: Resultados áReas Diagnóstico En Mesialización Molarunclassified
“…Similar amount of tip back bend was suggested by Chae and Kim 19 et al that is 20 to 30° while using a running loop for protraction of mandibular molar. Saga et al 20 also suggested that a 20° tip back bend should be given while mesializing mandibular molar using a helical loop. Narmada et al 21 in their case report applied a tip back angle on 20-30° but this caused the slight distal tipping of molar at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Por último es muy importante que el cierre del espacio se produzca sin lesionar los tejidos de sostén, por lo tanto, es deseable que el movimiento se realice sin que se formen áreas extensas de hialinización, que puedan dificultar y retrasar este movimiento, por lo que es necesario que la fuerza aplicada produzca un movimiento efectivo con las mínimas molestias y el mínimo daño a los tejidos (22).…”
Section: Discussionunclassified
“… Aumento de la sobremordida.  Estas anomalías pueden dificultar una posible rehabilitación protésica (22).…”
Section: Figura 2 Porcentaje De Los Tipos De Estudios De Los Artículo...unclassified